Integrated analysis of muscle lncRNA and mRNA of Chinese indigenous breed Ningxiang pig in four developmental stages - Chen, Wenwu; Yang, Fang; Liufu, Sui; Li, Zhi; Gong, Yan; Ma, Haiming (Frontiers in Veterinary Science, 2024)
Meat and its derivatives serve as crucial sources of protein, vitamins, minerals, and other essential nutrients for humans. Pork stands as China’s primary animal-derived food product consumed widely across diverse dietary structures; evaluating intramuscular fat content becomes pivotal in assessing its quality standards. Nonetheless, the intricate molecular mechanisms governing intramuscular fat deposition remain elusive. Our study utilized sequencing technology to scrutinize longitudinal development stages within Ningxiang pig’s longest dorsal muscles aiming to unravel these underlying mechanisms. In three distinct comparisons (30d vs. 90d, 90d vs. 150d and 150d vs. 210d) there were 578, 1,000 and 3,238 differentially expressed mRNA, along with 16, 158 and 85 lncRNAs were identified. STEM analysis unveiled six enriched model profiles for lncRNAs while seven such profiles emerged for mRNAs; notably, multiple shared model profiles existed between both RNA types. Enriched analysis highlighted numerous genes from mRNA profile8 and lncRNA profile7 significantly associated with pathways linked to fat deposition. Weight Gene Co-Expression Network Analysis (WGCNA) revealed that differential expression modules (DMEs) & differential expression lncRNAs primarily clustered within cyan, dark slate blue and pale turquoise modules. Furthermore, target genes PKD2 (MSTRG21592.MTRSG8859 and MTRSG18175), COL5A1 (MTRSG9969 and MTRSG180) and SOX13 (MTRSG21592 and MTRSG9088) as core components all intricately tied into processes related to fat deposition. This study lays the groundwork for deeper exploration into the molecular mechanisms underlying LDM fat deposition traits, and it also presents candidate genes for future molecular marker-assisted breeding.